2021
DOI: 10.1515/cclm-2021-1021
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis, epidemiology and biomarkers of susceptibility of pulmonary fibrosis in COVID-19 survivors

Abstract: Pulmonary fibrosis (PF), a pathological outcome of chronic and acute interstitial lung diseases associated to compromised wound healing, is a key component of the “post-acute COVID-19 syndrome” that may severely complicate patients’ clinical course. Although inconclusive, available data suggest that more than a third of hospitalized COVID-19 patients develop lung fibrotic abnormalities after their discharge from hospital. The pathogenesis of PF in patients recovering from a severe acute case of COVID-19 is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 60 publications
1
36
0
3
Order By: Relevance
“…A notable result of our study is that no patients showed further deterioration in respiratory function from 3 to 6 months to 1 year after admission. These data seem to suggest that changes in the pulmonary interstitium, frequently detected in the first months after the acute phase of COVID-19 [9], do not tend to worsen over time. The possible evolution into pulmonary fibrosis secondary to COVID-19 is a matter of concern [10].…”
Section: Discussionmentioning
confidence: 66%
“…A notable result of our study is that no patients showed further deterioration in respiratory function from 3 to 6 months to 1 year after admission. These data seem to suggest that changes in the pulmonary interstitium, frequently detected in the first months after the acute phase of COVID-19 [9], do not tend to worsen over time. The possible evolution into pulmonary fibrosis secondary to COVID-19 is a matter of concern [10].…”
Section: Discussionmentioning
confidence: 66%
“…The pathogenesis of COVID-19 in the lung includes an initial phase of local inflammation, endothelial cell damage, and antifibrinolytic activation in the upper and lower respiratory tracts, followed by repair mechanisms that can elicit the restoration of normal pulmonary architecture. Inflammation is followed by platelet recruitment with degranulation, clot formation, altered vessel permeability, and accumulation of leukocytes in the injury site, leading to the recruitment of other inflammatory cells with the involvement of specific cytokines (i.e., IL-4, IL-13, transforming growth factor-β) that are also responsible for pro-fibrotic activity ( 12 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 99%
“…Although not specific to pulmonary disease, several biomarkers of different stages of lung involvement in COVID-19 have been identified and have been associated with pulmonary and systemic hyperinflammation and fibrotic damage ( 12 ). In the early disease course, neuron-specific enolase (NSE) can be used to differentiate patients who are going to develop dyspnea ( 21 ).…”
Section: Diagnostic and Prognostic Value Of Biomarkersmentioning
confidence: 99%
“…In sharp contrast, COVID-19 pneumonia has affected millions of people worldwide, and even a very small proportion of patients with pulmonary fibrosis may represent a considerable clinical and health system problem. 5 Finally, viral infections have been associated (indirectly) with pulmonary fibrosis. 6 …”
Section: Will Patients Who Had Severe Covid-19 Develop Pulmonary Fibr...mentioning
confidence: 99%
“…Special attention will be required in individuals with some putative risk factors such as male gender, aging, active smoking, 5 accelerated biological age, and abnormal telomere shortening. 7 …”
Section: Will Patients Who Had Severe Covid-19 Develop Pulmonary Fibr...mentioning
confidence: 99%